Statistical analysis of the critical quality attributes of 1,2- dihydroxypropane as a pharmaceutical excipient - Mostafa Essam Ahmed Mostafa Eissa (German Journal of Pharmaceuticals and Biomaterials, 2024)
The constituting ingredients, either active or inactive, directly influence the quality and efficacy of the pharmaceutical medicinal product. One of the most common and versatile excipients used in various industries, including pharmaceuticals, is 1,2-propanediol, propylene glycol, or methyl ethyl glycol. The present work aims to trend the quality characteristics of Methyl ethyl glycol using exploratory process-behavior plots, which are graphical tools for monitoring and improving process performance. This study focused on the assay and water content tests of the initial 34 batches of the manufactured 1,2-Propanediol using a standard analysis method according to the British Pharmacopoeia (BP), which specifies this excipient's quality requirements and limits. Exploratory Shewhart charts, the simplest and most widely used control charts, were plotted using Statistical Process Control (SPC) software. The results showed that the data did not follow a normal distribution, and there were several out-of-control signals from both quality aspects, indicating that the process was unstable and unpredictable even if no results exceeded the specifications criteria. The study suggests that the supplier needs to improve the process control and the quality limits of Methylethylene glycol to ensure its consistency and reliability. The application of SPC techniques is essential for the modern, competitive chemical industry, as they help to reduce variability, enhance quality, and optimize resources. Trending charts provide a quantitative estimation of the current situation and the actions needed for the future improvement of the quality control tests. Future research could explore the impact of the quality variation of 1,2-Propanediol on the performance and stability of the final dosage forms, as well as the potential risks and benefits of using alternative excipients with similar properties.